2013
DOI: 10.1080/ac.68.5.2994468
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between endothelial nitric oxide synthase 4a/4b gene polymorphism and premature coronary artery disease

Abstract: The eNOS4a/b gene polymorphism may be associated with early development of atherosclerosis and myocardial infarction possibly secondary to deterioration of the endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
7
1
5
Order By: Relevance
“…1 Besides atherosclerosis and inflammatory tissue diseases mentioned above, in ≈20% to 30% of CAE cases a congenital origin has been postulated. 5 Genetic predisposition of CAE could be suggested from its association with polymorphisms in HLA-DR B1 and DQ B1, 36 angiotensin-converting enzyme DD genotype, 37 endothelial nitric oxide synthase gene, 38 as well as associations with various hereditary conditions, such as familial hypercholesterolemia, 39 isolated congenital coronary artery fistulas, 40 and heritable connective tissue disorders, such as Marfan syndrome and Ehlers-Danlos syndrome. 15,16 Data by our own group also revealed frequent appearance of ectatic CAD in subjects with a strong positive family history of MI.…”
Section: Discussionmentioning
confidence: 99%
“…1 Besides atherosclerosis and inflammatory tissue diseases mentioned above, in ≈20% to 30% of CAE cases a congenital origin has been postulated. 5 Genetic predisposition of CAE could be suggested from its association with polymorphisms in HLA-DR B1 and DQ B1, 36 angiotensin-converting enzyme DD genotype, 37 endothelial nitric oxide synthase gene, 38 as well as associations with various hereditary conditions, such as familial hypercholesterolemia, 39 isolated congenital coronary artery fistulas, 40 and heritable connective tissue disorders, such as Marfan syndrome and Ehlers-Danlos syndrome. 15,16 Data by our own group also revealed frequent appearance of ectatic CAD in subjects with a strong positive family history of MI.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies showing significant or insignificant associations between the eNOS gene polymorphism and premature CAD (26)(27)(28)(29). Ekmekci et al concluded that the eNOS 4a/b gene polymorphism was significantly higher in ST elevation myocardial infarction patients, but this polymorphism was not found to be an independent predictor for aortic dissection (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…В работе N. Sivri et al [23] обнару-жена корреляция между полиморфизмом 4а/b и риском развития ишемической болезни сердца. Наличие аллеля «а» полиморфизма 4а/b является независимым предиктором инфаркта миокарда с элевацией сегмента ST у лиц молодого возрас-та (ОШ=2,78, 95% ДИ=1,02-7,56, р=0,044) [31]. Проведенный A. Ekmekci et al [32] одномерный анализ, в котором генотип 4b4b был использован в качестве референтного, показал, что наличие аллеля «а» в полиморфизме 4а/b в значительной степени предопределяет развитие феномена за-медления коронарного кровотока (ОШ=2,79, 95% ДИ=1,32-5,89, р=0,007) у лиц, входящих в группу риска, а в многомерном анализе с исполь-зованием модели с поправкой на переменные со значением р ниже чем 0,10 однофакторного ана-лиза, установлено, что наличие аллеля «а» явля-ется независимым прогностическим фактором возникновения феномена замедления коронар-ного кровотока (ОШ=3,22, 95% ДИ=1,28-8,82; р=0,013), кроме того, наличие в генотипе аллеля «а» может быть фактором риска развития микро-сосудистой эндотелиальной дисфункции у паци-ентов с замедлением коронарного кровотока.…”
Section: характеристика полиморфного локуса т786с гена эндотелиальнойunclassified